(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
Virus outbreaks such as the COVID-19 virus demand nutrition interventions among people all over the world. Consumption of foods with immune-modulating and nutraceutical characteristics is an effective strategy to avoid or lessen the severity of viral attacks and side effects. Immune stimulants function by enhancing macrophage activity and killing pathogens and diseased cells, while adaptogens work by supporting and regulating the endocrine system. This paper foreshadows the use of mushrooms as a functional food for the prevention and treatment of COVID – 19 by citing peer-reviewed papers from Google Scholar, PubMed, the WHO database, Science direct, and the author’s own research. Pleurotus ostreatus, Termitomyces heimii, T. microcarpus, T. clypiatus, Auricularia auricula, Phlebopus portentos, Ganoderma lucidum, Coprinus micaceus, Cantharellus cibarius, C. minor, and Lentinus bambusinus were among the ethnomedicinal mushrooms studied. Immuno-modulating effects were found in polysaccharides, fungal immune-modulatory proteins (FIPs), terpenes, and terpenoids from wild mushrooms, as well as activation of immune effector cells such as lymphocytes, macrophages, and natural killer cells. They also cause the production of cytokines such as IFN-, IL-2, IL-4, IL-10, and TNF-. Similarly, mushrooms have been shown to have probiotic properties that can help to flatten the curve.